Robotic arm control using voice signal - Norulhuda Daud (Universiti Malaysia Perlis, 2008)
A voice-based system has been developed to control a robot arm using oral commands. The system is divided into two main components: speech recognition engine and robotic control unit. In the speech recognition engine, a microphone is used to record the voice samples from the speakers. From the recorded speech signals, the formant frequencies are computed and used as features for training the neural network. A simple neural network model is developed to associate the input features and the output voice sample. After the recognition of speech or voice signal, the control signal is gave through microcontroller to control the robot arm. The developed controller is based on a neural network system.